The Correlation between Serum Levels of Anti-Toxoplasma gondii Antibodies and the Risk of Diabetes - Maryam KHALILI; Mahmoud MAHAMI-OSKOUEI; Abbas SHAHBAZI; Abdolrasoul SAFAIYAN; Nader MOHAMMADZADEH-GHESHLAGHI; Leyla MAHAMI-OSKOUEI (Iranian Journal of Parasitology, 2018)
Background: This study investigated the presence of specific antibodies against Toxoplasma gondii infection among people with diabetes (type I and II) in comparison with control group.